Rotatividade no setor de call center: narrativa dos ex-funcionários a respeito dos fatores causadores do turnover - Isalto, Karine de Lima (Universidade Federal Rural do Semi-Árido, 2018)
High turnover rates can significantly compromise an organization's results. In general and based on this idea, the studies favor the version of the organization to identify the factors of the same. This study, however, gives emphasis to another narrative and sought to analyze the factors that cause turnover from the discourse of former employees. A qualitative research was carried out in a call center in the city of Mossoró / RN, interviewing six former employees and comparing their narratives with the justifications present in the organization's documents. The data were transcribed, categorized and an interpretative analysis was performed. The results pointed out that the main causes of turnover are organizational factors, ex-employees' dissatisfaction regarding salary, benefits, supervisors and managers, and pressure for goals and results
Monografia
Keywords: Rotatividade; Call Center; Gestão de Pessoas; Turnover; Call Center; People Management; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO